2013
DOI: 10.1002/maco.201307346
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational studies of two antibacterial drugs as corrosion inhibitors for mild steel in acid media

Abstract: The inhibition of mild steel corrosion in 3% HCl solution by sulfamethoxazole (SZ) and norfloxacin (NF) were investigated at 25 8C using weight loss measurement. The measurements reveal that the inhibition efficiency grows with increasing concentrations of inhibitors, and the inhibition efficiency decreases in the order NF > SZ. The adsorption of inhibitor molecule on mild steel surface follow Langmuir isotherm. Quantum chemical calculation was performed to correlate electronic structure parameters of SZ and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Therefore, the change in the C dl values originated from the gradual displacement of the water molecules by the adsorption of the corrosion inhibitors on the iron surface, decreasing the extent of metal dissolution. 33 Overall, the corrosion inhibition performances obtained from the EIS measurements are in good agreement with those obtained from PDP.…”
Section: Eis Measurementssupporting
confidence: 69%
“…Therefore, the change in the C dl values originated from the gradual displacement of the water molecules by the adsorption of the corrosion inhibitors on the iron surface, decreasing the extent of metal dissolution. 33 Overall, the corrosion inhibition performances obtained from the EIS measurements are in good agreement with those obtained from PDP.…”
Section: Eis Measurementssupporting
confidence: 69%
“…In order to reduce the undesirable carbon steel dissolution by these processes and as the most effective and economic method, corrosion inhibitors are widely employed . The new generation of environmental regulation requires the replacement of toxic inhibitors with non‐toxic inhibitors . In view of this, many alternative ecofriendly corrosion inhibitors have now been developed.…”
Section: Introductionmentioning
confidence: 99%
“…A good solution to this problem is to use corrosion inhibitors due to their excellent inhibition efficiency and considerable economic benefit. The reported inhibitors against steel corrosion in acidic medium are usually heterocyclic organic compounds containing highly electronegative atoms in their molecular structures, such as nitrogen, oxygen, sulfur, phosphorus, unsaturated bonds, or large conjugation system . Singh et al reported that quinoline derivatives with different substituent groups (e.g., hydroxyl, sulfhydryl, amino, and phenyl) on the quinoline ring could inhibit the Q235 steel corrosion in acidic medium, in which the corrosion inhibition occurs due to the adsorption of inhibitor molecules on the steel surface and the differences in the inhibition properties were attributed to the different molecular structures of inhibitors.…”
Section: Introductionmentioning
confidence: 99%